Clinical pharmacist-led problem-specific education as a strategy for addressing suboptimal antimicrobial use in intensive care unit: a prospective pre-post analysis - İlerler, Enes Emir; Ayhan, Yunus Emre; Yalçinkaya, Erdem; Karakurt, Sait; Sancar, Mesut (Frontiers in Pharmacology, 2025)
BackgroundAntimicrobial use in ICUs is challenging due to altered pharmacokinetics, severe infections, and the burden of comorbidities. This study aims to investigate the contribution of clinical pharmacy services in reducing antimicrobial drug therapy problems (ADTPs) in the intensive care unit.MethodsThis study was a prospective, pre-post intervention study conducted over a total duration of 6 months (15 January 2023–15 July 2023) in Türkiye. During both control period (CP) and intervention period (IP), ADTPs were identified and classified according to established definitions describing each day of therapy with a specific antimicrobial agent. In IP, clinical pharmacist-led services were implemented for the ICU team, encompassing problem-targeted educational sessions and bedside intervention recommendations.ResultsA total of 85 patients (CP, n = 43; IP, n = 42) were included in the study. The mean age of the patients was 68.87 years (SD = 16.09). The most common indication for antimicrobial initiation was pneumonia (56.5%), while the most frequently used antimicrobial agent throughout the study was piperacillin-tazobactam (44.7%). It was found that 5.5% of patients across all periods received unnecessary, 2.2% inappropriate, and 92.3% sub-optimal antimicrobial therapy. During both CP and IP, almost all ATDPs were categorized under sub-optimal treatment problems related to medication dosage and/or administration regimens (93.94% vs. 88%). A statistically significant 62% reduction in total ADTPs was observed during IP compared to CP (total ADTPs, 66 vs. 25; p = 0.001).ConclusionThis study identified a high incidence of ADTPs in the ICU, with the majority classified as sub-optimal. The significant reduction in ADTPs observed between the periods with the provision of clinical pharmacy services highlights the effective role of clinical pharmacists in reducing ADTPs.